AVAILABILITY OF FEED TO SUPPORT BUFFALO DEVELOPMENT IN INDONESIA - Winugroho, M.; Widiawati, Yeni (Proceeding Buffalo International Conference, 2013)
Evaluation of feed availability is important to estimate carrying capacity in any given areas to support proper buffalo production. For the last few years climatic global change has enlarged drier areas and consequently lower crop production. Changing in crop patterns such as planting and harvesting are expected to change pattern of monthly feed availability. Land conversion in Jawa can be up to 40,000 Ha per year while in outer Jawa huge land is converted into crop estates such as palm oil and rubber plantation. This will affect types of feed ingredients which should be closely studied in conjunction to buffalo reproduction. The role of agricultural and industrial by-products as feedstuffs can be estimated but production of natural green forages is still hard to estimate. Furthermore, the way how to manage buffaloes is likely to be also affected by the land scarcity. Communal house may be as the alternative for the extensive system so far we know. High meat demand has reduced beef cattle population and hence buffalo numbers. International collaboration on buffalo production and reproduction are suggested.